A Novel Graphene Quantum Dot‐Based mRNA Delivery Platform. Issue 7 (7th April 2021) - Liu, Ya; Zhao, Changhong; Sabirsh, Alan; Ye, Lilei; Wu, Xiaoqiu; Lu, Hongbin; Liu, Johan
Abstract: Abstract : During the last decades, there has been growing interest in using therapeutic messager RNA (mRNA) together with drug delivery systems. Naked, unformulated mRNA is, however, unable to cross the cell membrane and is susceptible to degradation. Here we use graphene quantum dots (GQDs) functionalized with polyethyleneimine (PEI) as a novel mRNA delivery system. Our results show that these modified GQDs can be used to deliver intact and functional mRNA to Huh‐7 hepatocarcinoma cells at low doses and, that the GQDs are not toxic, although cellular toxicity is a problem for these first‐generation modified particles. Functionalized GQDs represent a potentially interesting delivery system that is easy to manufacture, stable and effective. Abstract : Message delivered ! A novel graphene quantum dots based mRNA drug delivery platform was prepared. The results show that these modified GQDs can deliver intact and functional mRNA to Huh‐7 hepatocarcinoma cells at low doses. The transfection efficiency for FGQDs/mRNA complexes was 25 % with a formulation concentration of 4000 ng mRNA/mL, but comparable transfection efficiencies could be achieved at much lower doses if the ratio between carrier and cargo was optimized. This work describes the first steps towards a potentially interesting preparation method for stable and effective mRNA delivery systems.